Role of Extratropical Wintertime Cyclones in Regulating the Variations of Baffin Bay Sea Ice Export. Issue 5 (5th March 2021) - Liang, Yu; Bi, Haibo; Wang, Yunhe; Huang, Haijun; Zhang, Zehua; Huang, Jue; Liu, Yanxia
Abstract: A cyclone is an intensive synoptic activity that occurs frequently over Baffin Bay. By modifying the large‐scale distribution pattern of sea level pressure, a passing cyclone can serve as an important regulator of sea ice outflow via the Davis Strait. We obtain a nearly 40‐year‐long record (1979/1980–2017/2018) of the sea ice area flux (SIAF) through the Davis Strait and Arctic cyclone activities in winter. A case study and statistical results indicate that the sea ice concentration and motion fields can be greatly altered by the occurrence of cyclones, thereby contributing to changes in sea ice export. Moreover, the effects of cyclones on sea ice export in Baffin Bay are dependent on the spatial distribution pattern of the storms. In terms of the cyclone center count and intensity, the key regions with significant impacts on sea ice export out of Baffin Bay are identified, one around Baffin Island (80°W–60°W, 60°N–70°N) and the other over the southern Labrador Peninsula (70°W–50°W, 40°N–60°N). A robust correlation exists between the winter‐accumulated SIAF via the Davis Strait and the average winter cyclone intensity (center count) in the critical regions with R  = −0.57 (+0.49), affirming the vital role of cyclone activity in modulating the interannual variability of sea ice export in Baffin Bay. Key Points: The wintertime sea ice area flux through the Davis Strait and cyclone activities nearby over the period 1979/1980–2017/2018 are acquired Strong winds induced by cyclones can change the characteristics of sea ice and thus can impact sea ice export through the Davis Strait The effects of cyclones on sea ice export through the Davis Strait are spatially dependent, and the key regions are identified